let me try to help you this. although its bit difficult for me to explain it with paper and pen.
when ever you have any truth tableand you want to derive the formula, take all thos rows in which output F is one.
Here F is 1 for three rors
a) P = 0 and Q = 0
b) p = 0 an Q = 1
c) p= 1 and Q = 0
now take each term in binary and add them to get expression f\of F.
a) P = 0 and Q = 0 means
b) p = 0 an Q = 1 means
Let me know if teh concept is still not clear. I will explain you taking more examples.
c) p= 1 and Q = 0 means
So expression for F would be F = + +
which on simplification gives =